Odpowiedź :
a)
[tex]2 \frac{1}{2} \div 5 - \frac{1}{3} = \frac{5}{2} \times \frac{1}{5} - \frac{1}{3} = \frac{1}{2} \times 1 - \frac{1}{3} = \frac{1}{2} - \frac{1}{3} = \frac{3}{6} - \frac{2}{6} = \frac{1}{6} [/tex]
b)
[tex](3 \frac{1}{3} + \frac{5}{9} ) \div 7 =(3 \frac{3}{9} + \frac{5}{9} ) \div 7 = 3 \frac{8}{9} \times \frac{1}{7} = \frac{35}{9} \times \frac{1}{7} = \frac{5}{9} \times 1 = \frac{5}{9} [/tex]
c)
[tex](1 \frac{4}{7} - 1 \frac{1}{3} ) \div 10 = (1 \frac{12}{21} - 1 \frac{7}{21} ) \div 10 = \frac{5}{21} \div 10 = \frac{5}{21} \times \frac{1}{10} = \frac{1}{21} \times \frac{1}{2} = \frac{1}{42} [/tex]
d)
[tex](5 \frac{1}{5} - 2 \frac{3}{4} ) \div {2}^{2} = (5 \frac{4}{20} - 2 \frac{15}{20} ) \div 4 =( 4 \frac{24}{20} - 2 \frac{15}{20} ) \div 4 = 2 \frac{9}{20} \times \frac{1}{4} = \frac{49}{20} \times \frac{1}{4} = \frac{49}{80} [/tex]
e)
[tex]((2 \frac{1}{2} ) ^{2} - \frac{3}{4} ) \div 11 = (( \frac{5}{2} ) ^{2} - \frac{3}{4} ) \div 11 = ( \frac{25}{4} - \frac{3}{4} ) \times \frac{1}{11} = \frac{22}{4} \times \frac{1}{11} = \frac{2}{4} \times 1 = \frac{2}{4} [/tex]
f)
[tex](2 \frac{1}{3} ) ^{2} \div 7 - \frac{2}{3} = (\frac{7}{3} )^{2} \div 7 - \frac{2}{3} = \frac{49}{9} \div 7 - \frac{2}{9} = \frac{49}{9} \times \frac{1}{7} - \frac{2}{3} = \frac{7}{9} \times 1 - \frac{2}{3} = \frac{7}{9} - \frac{2}{3} = \frac{7}{9} - \frac{6}{9} = \frac{1}{9} [/tex]
Myślę że pomogłem ;)
Odpowiedź:
2 i 1/2 : 5 - 1/3 = 5/2 * 1/5 - 1/3 = 1/2 - 1/3 = 1/6
(3 i 1/3 + 5/9) : 7= (3 i 3/9 + 5/9) : 7= 3 i 8/9 : 7 = 35/9 * 1/7 = 5/9
(1 i 4/7 - 1 i 1/3) : 10 = ( 1 i 12/21 - 1 i 7/21) : 10 = 5/21 * 1/10 = 1/42
(5 i 1/5 - 2 i 3/4) : 2² = (5 i 4/20 - 2 i 15/20) : 2² = (4 i 24/20 - 2 i 15/20) : 4 = 2 i 9/20 *1/4 = 49/20 * 1/4 = 49/80
(( 2 i 1/2)² - 3/4) : 11 = ((5/2)² - 3/4) : 11 = (25/4 - 3/4) : 11 = 22/4 * 1/11 = 2/4 = 1/2
( 2 i 1/3)² : 7 - 2/3 = (7/3)² : 7 - 2/3 = 49/9 * 1/7 - 2/3 = 7/9 - 2/3 = 7/9 - 6/9 = 1/9